Reduction of maggot feed nutrients by mussel (Pilsbryoconcha exilis) on the Integrated Multi Thropic Aquaculture (IMTA) system - Asti Astuti Putri; Arnold Kabangnga; Heriansah Heriansah (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
Increasing the productivity of aquaculture must be supported by feed input; however, in addition to being expensive, this input can produce nutrient waste. Therefore, finding inexpensive alternative forms of feed with environmentally friendly cultivation practices is important to do simultaneously. This study aimed to determine the effect of variations in the form of maggot feed on the Nutrient Reduction Efficiency (NRE) of freshwater clams (Pilsbryoconcha exilis) in an integrated multitrophic aquaculture (IMTA) system. This 28 day experiment used a Completely Randomized Design (CRD) with four types of feed treatments (live maggots, dried maggots, supplemented maggots, and commercial feed (control). A total of 10 individuals of freshwater clams combined with 10 tilapia fish and freshwater lobsters respectively, as well as 4 clumps of rice were floated in a rearing tank with a volume of 50 L of fresh water. The results of analysis of variance showed that variation in feed had a significant effect (P<0.05) on the NRE of ammonia (NH3), nitrate (NO3), phosphate (PO4) by freshwater clams (Pilsbryoconcha exilis). Tukey HSD test results indicated that the highest NRE of ammonia (NH3) in live maggots feed was significantly different (P<0.05) from dried maggot feed and supplemented maggots, but not significantly different (P>0.05) from commercial feed. NRE nitrate (NO3) was significantly different in each treatment. Meanwhile, the highest NRE phosphate (PO4) in live maggots feed was not significantly different (P>0.05) from dried maggots, but was significantly different (P<0.05) from supplemented maggots and commercial feed.